Witnessing as pedagogy: Translating Indigenous knowledges into practice - Louie, Dustin William; Poitras Pratt, Yvonne; Luggi, Terry Lynn (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2026)
We believe Indigenous witnessing provides an impactful exemplar of how to translate Indigenous Knowledges into pedagogy that challenges the normalization of Western knowledge systems. By sharing our Indigenizing process of witnessing with fellow educators within a mandatory post-secondary Indigenous Education course to a foundation of Indigenous Knowledges, we hope to inspire meaningful authentic practices within local context grounded in Indigenous ways of knowing. Our theoretical framework posits that transformational Indigenous pedagogies can emerge from educators’ ethical positioning and ability to see possibilities between the specific educational aims of their course(s) and translating local Indigenous Knowledges into practical pedagogical approaches.